The Dynamics of Self-Quality and Partner Perception in Predicting Swiping Intentions - Mia Audina Olivia (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2026)
This qualitative study delves into the user’s comprehension and interpretation of their own qualities and those of potential partners during the decision-making process of online dating applications. Employing an exploratory design, in-depth interviews were conducted with six purposively selected participants. The analysis employed a thematic approach, utilizing Saldaña’s coding cycle. This approach commenced with initial/open coding and progressed to focused/axial coding. The study presents four key insights. Firstly, users construct their self-quality through a combination of physical appearance, personal competencies, and feedback received from other users. These factors collectively shape their self-image within the digital dating environment. Secondly, the quality of potential partners is assessed through rapid judgments based on photographs, profile information, personal values, and perceived compatibility. Thirdly, swiping decisions are influenced by subjective interpretations, emotional states, and reflections that arise after interactions. Lastly, users perceive the online dating environment as a competitive space that impacts their strategies, standards, and self-worth. Collectively, these findings indicate that swiping is not a mere technical action, but a cognitive and emotional process shaped by the interplay of individual factors, digital contexts, and social experiences.